Sensory quality attributes of microwave vacuum concentrated pineapple juice - Kumar, Ashok; Kulshrestha, Rewa (Journal of Postharvest Technology, 2023)
Pineapple (Ananas comosus L.) is one of the commercially important fruit crops of India which is preferred by many people due to its pleasant aroma, flavor and refreshing sugar–acid balance. Concentration of pineapple juice is used to reduce the transportation, packaging and storage cost as well as to ensure off-time availability of juices. In this work, pineapple juice was concentrated by microwave vacuum evaporation process up to 50 brix. The sensory quality attributes of reconstituted pineapple juice was evaluated and compared with fresh pineapple juice and one of the packaged pineapple juices available commercially in the market. The sensory data were analyzed by using fuzzy logic to find out the relative importance of the quality attributes of pineapple juice samples in general, ranking of the pineapple juice samples and ranking of individual quality attributes of each of the pineapple juice samples tested. The results of fuzzy logic revealed that reconstituted pineapple juice was comparable with fresh pineapple juice in terms of sensory quality attributes taste, mouthfeel and colour on 6-point sensory scale. The aroma attribute of reconstituted pineapple juice was lower than the fresh pineapple juice on 6-point sensory scale. Microwave vacuum evaporation process used for concentration of pineapple juice was better option than thermal vacuum evaporation process.